Tinjauan Ekonomi Islam Terhadap Manajemen Keuangan Sekolah: Studi Kasus MTS Al-Baisyuni Sungai Ambawang - Asri Safitri (Tauhidinomics: Journal of Islamic Banking and Economics, 2026)
This study examines the implementation of Islamic economic principles in school financial management, focusing on a case study at MTs Al-Baisyuni Sungai Ambawang. It aims to analyze how prophetic values—particularly Shiddiq (honesty) and the avoidance of gharar (uncertainty)—are applied in managing educational funds under resource constraints. Using a qualitative approach with data triangulation, the findings show that the school promotes transparency by involving the committee in budget planning (RAPBS) and disseminating financial reports during the imtihan forum. However, the full implementation of Islamic economic principles remains limited due to challenges such as inadequate human resources, insufficient infrastructure, regulatory constraints in accessing BOS funds for private schools, and unstable funding following the exemption of tuition fees for low-income students. The study concludes that despite strong moral commitment, systemic support and managerial training are essential to enhance sharia-based nonprofit financial governance.